The Alcohol Dehydrogenase Gene Family in Melon (Cucumis melo L.): Bioinformatic Analysis and Expression Patterns - Jin, Yazhong; Zhang, Chong; Liu, Wei; Tang, Yufan; Qi, Hongyan; Chen, Hao; Cao, Songxiao (Frontiers in Plant Science, 2016)
Alcohol dehydrogenases (ADH), encoded by multigene family in plants, play a critical role in plant growth, development, adaptation, fruit ripening and aroma production. Thirteen ADH genes were identified in melon genome, including 12 ADHs and one formaldehyde dehydrogenease (FDH), designated CmADH1-12 and CmFDH1, in which CmADH1 and CmADH2 have been isolated in Cantaloupe. ADH genes shared a lower identity with each other at the protein level and had different intron-exon structure at nucleotide level. No typical signal peptides were found in all CmADHs, and CmADH proteins might locate in the cytoplasm. The phylogenetic tree revealed that 13 ADH genes were divided into 3 groups respectively, namely long-, medium- and short-chain ADH subfamily, and CmADH1,3-11, which belongs to the medium-chain ADH subfamily, fell into 6 medium-chain ADH subgroups. CmADH12 may belong to the long-chain ADH subfamily, while CmFDH1 may be a Class III ADH and serve as an ancestral ADH in melon. Expression profiling revealed that CmADH1, CmADH2, CmADH10 and CmFDH1 were moderately or strongly expressed in different vegetative tissues and fruit at medium and late developmental stages, while CmADH8 and CmADH12 were highly expressed in fruit after 20 days. CmADH3 showed preferential expression in young tissues. CmADH4 only had slight expression in root. Promoter analysis revealed several motifs of CmADH genes involved in the gene expression modulated by various hormones, and the response pattern of CmADH genes to ABA, IAA and ethylene were different. These CmADHs were divided into ethylene-sensitive and –insensitive groups, and the functions of CmADHs were discussed.